(untitled) (Research, Society and Development, 2020)
Regulatory B cells (Bregs) are cells that modulate the immune response through secretion of interleukins such as IL-10, IL-35 and TGF-β. Different subsets of Breg cells vary not only in their phenotype, but also in their action mechanism. Studies have identified the presence of Breg cells during the development of some types of tumors. The aim of this paper is to survey the literature on some of the Bregs cell’s phenotypes, their origin and their immune response modulation mechanisms, as well as their role in some types of tumors. Regarding methodology, the SciELO and PubMed databases and theirs descriptors “regulatory B cells”, associated with “IL-10” and “tumor immunity” were used in order to survey both original and review articles. We found 108 articles referring to the subject from which 74 articles were selected taking into consideration the objectives proposed for this review. We conclude that there are several phenotypes of Breg cells and that these cells act mostly through immunosuppression mechanisms, thus enabling the development and progression of some diseases, such as cancer. Understanding the mechanisms by which Breg cells influence the immune response profile in certain diseases is important for designing safe and effective immunotherapies targeted at these cells.